Sustaining Water Resources: A Study on Conservation Efforts in Taman Merlimau Bestari - Ismail, Hassan (Jurnal Civil Engineering Study, 2025)
This study examines water use efficiency in the residential area of Taman Merlimau Bestari, Melaka, in response to the threat of water shortages exacerbated by extreme hot weather. Rising temperatures have led to increased water consumption, raising concerns about sustainability and the potential for future water scarcity. The main focus of the research is to analyze the impact of household water usage during heat stress periods. The study's objectives include evaluating current water consumption habits, promoting awareness of water conservation practices, and assessing the effectiveness of these efforts through the analysis of monthly water bills. Data was collected via random sampling, using questionnaires distributed to residents, along with monthly water bill records from Syarikat Air Melaka Berhad (SAMB). After implementing awareness programs, results showed a significant reduction in water consumption, as reflected in lower water bills. The findings indicate that increasing awareness among residents plays a crucial role in improving water use efficiency, which can help reduce pressure on local water resources during extreme heat events. The study highlights the importance of ongoing education and proactive water management in addressing water scarcity challenges in Melaka.